BIOGAS DARI CAMPURAN LIMBAH AMPAS TAHU DAN KOTORAN SAPI : EFEK KOMPOSISI DAN VOLATIL SOLID - , Lailan Nimah, Ir. Agus Prasetya, M.Eng., Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The increasing of energy demand and the decreasing of fossil fuel cause the energy crisis. Therefore, the innovation is needed to invent an alternative energy. One of the alternative energy is biogas which can be produced from solid waste of tofu production (SWTP). The SWTP utilizing to produce biogas can reduce the fossil fuel consumption and reduce the environmental pollution because the majority of SWTP directly discarded to environment. The decreasing of pH biogas production process from SWTP cause the methanogen cannot be survive therefore it needs buffer, one of material that can be used as buffer is cow manure. The biogas is produced trough organic compound cracking which employ anaerobe microorganism activity in a biodigester. The experiment was done in a batch anaerobic reactor. As many as 800 ml of sample was entered to the reactor with the capacity of 1 L, then incubated in an anaerobic condition in the room at the temperature of 25-30o The experiment result shows that the composition of cow manure and SWTP at VS of 3% KS:AT = 50:50 shows the highest methane concentration compared to the other compositions. The mathematic model as first order of reaction rate equation can approach the experiment result.